STRATEGI MANAJEMEN KOMUNIKASI KEPALA SEKOLAH SEBAGAI PEMIMPIN DALAM MEMOTIVASI KERJA BAWAHAN DENGAN BERLANDASKAN PADA HADIS NABI SAW - Junaid, Junaid Bin (Department of Islamic Education Management, 2023)
Communication is a very fundamental activity in human life. The human need to relate to each other is recognized by almost all religions as having existed since Adam and Eve. Human nature to convey his desires and to know the desires of others, is the beginning of human skills to communicate automatically through symbols, signs, then followed by the ability to give meaning to each of these symbols in the form of verbal language. Like what is contained in the behavior of a school principal. where the leadership of the Principal determines the quality of a school he leads and is accompanied by a communication management strategy. Because in general, subordinates always follow and obey the directions given and mandated by the Principal. And this must be accompanied by a qualified strategy. As in the second foundation of Islamic teachings it is revealed that a leader has great responsibility for the tasks carried out.